PTH-093 One year mortality outcomes of patients with liver cirrhosis admitted to a teaching hospital intensive care unit. (22nd June 2015) - Tai, D; Lewis, H; Derwa, Y; Lillis, A; Reynolds, T; Maitland, K; Hall, D; Alazawi, W; Foster, GR; Hadley, JS
Abstract : Introduction: Cirrhotic patients admitted to the intensive care unit (ICU) are reported to have poor outcomes with published one year mortality rates of up to 81%. 1 ICU mortality in cirrhotic patients has improved over recent years, but there is no recent data on one year outcomes. The aim of this study was to examine one year mortality, assess organ and liver scoring systems predictive value for one year mortality and to compare outcomes in patients with alcohol and non-alcohol related cirrhosis admitted to the ICU of a non-transplant tertiary Hepatology centre. Method: This was a retrospective analysis of prospectively collected data on outcomes of consecutively admitted patients with liver cirrhosis to the Royal London Hospital, from Intensive Care National Audit and Research Centre records. Results: Between 01/01/2006 and 31/12/2013, 253 cirrhotic patients were admitted to ICU. The most common reasons for admission were sepsis (33%), GI bleed (24%) and hepatic encephalopathy (11%). Aetiologies of cirrhosis included alcohol (68%), viral hepatitis (17%) and NASH (4%). There were significant differences in median age (53 vs 57), ethnicity (White/Black/Asian – 87/5/8% vs 56/13/31%) and admissions for sepsis (38% vs 21%) between those with alcohol and non-alcohol related aetiologies. One year, hospital and ICU mortality were 66%, 57% and 39% overall, 66%, 58% and 40% in alcohol, and 66%, 54% and 38% in non-alcohol aetiologies of cirrhosis respectively (p=ns.). 1 year mortality in patients requiring 1, 2, 3 and 4 organ support was 49%, 68%, 95% and 88%. Patients requiring renal replacement therapy (RRT) had more organs failing (3 vs 1 p < 0.0001) and a higher MELD score (19 vs 15 p < 0.005) compared to those not requiring RRT. ICU, hospital and one-year mortality was 70%, 86% and 89% in this group. The SAPS II score was a better predictor of one-year mortality than other organ failure scores. Conclusion: One-year mortality in our series compares favourably with the 81% previously reported in a UK transplant centre, 1 and most patients who survive hospital admission will survive to one year. Patients with alcohol and non-alcohol aetiologies of cirrhosis have similar outcomes. The requirement for RRT bestows a poor prognosis. Organ failure scores, particularly the SAPS II, are better at predicting one year mortality than the MELD score, but their discriminatory power was relatively poor. Disclosure of interest: None Declared. Reference: Mackle IJ et al . One year outcome of intensive care patients with decompensated alcoholic liver disease. Critical Care 2006;97:49–8